If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 0.5(x + -3) * 2 Reorder the terms: y = 0.5(-3 + x) * 2 Reorder the terms for easier multiplication: y = 0.5 * 2(-3 + x) Multiply 0.5 * 2 y = 1(-3 + x) y = (-3 * 1 + x * 1) y = (-3 + 1x) Solving y = -3 + 1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -3 + 1x
| 3(x^2)-4x-69=0 | | 2x-118=50 | | -16t^2+14t+240=0 | | y+(-6)=-24 | | 9x^2+12x=45 | | y^2+6+8= | | z^2-5z-36= | | 14=2b-2 | | 9x^2-73x+70=0 | | 7.38=.4x+5.34 | | 6+3y=-2 | | .0015x=50000 | | x*2+4x+1=0 | | 2x-5(x+4)=-6+4x-19 | | 39-2x=11-9x | | z^2-5z+24= | | =-3x-4 | | 3p^2-9p-120=0 | | 72+6x=x^2 | | 015x=50000 | | 36-4(5)(9)=0 | | a^7-a=0 | | -3e=6 | | -4x+9-5(x-1)=-(3x-6)-5x+5 | | 5(x-2)+18y=14x | | ln(7x-12)=3 | | 11x-6=9x+8 | | 4x+7-2x=8+3x-5 | | 35b-9m=3r+2 | | 15n=10n+25 | | 0.25N= | | W+4=(-9) |